Nursing management of successful extubation in a critically ill patient receiving mechanical ventilation for intractable laryngeal edema (1例顽固性喉头水肿人工辅助通气的重症患者成功脱机拔管的护理体会) - ZHANG Jing (张静); HAN Guyue (憨古月) (Association of Integrative Nursing, 2023)
This paper summarized the nursing management of successful extubation in a critically ill patient receiving mechanical ventilation for intractable laryngeal edema. An emergency plan and procedure for extubation after mechanical ventilation for intractable laryngeal edema was made and strictly implemented. Comprehensive nursing interventions such as illness condition observation, airway management, medication care, nutrition support, basic care and health education were carried out to ensure the successful extubation and postoperative rehabilitation. (本文总结1例顽固性喉头水肿且持续人工辅助通气的重症患者成功脱机拔管的护理经验。通过制定顽固性喉头水肿脱机拔管的应急预案及流程, 积极准确落实各项护理措施, 密切观察病情变化, 做好人工气道机械通气管理、用药护理、营养支持、基础护理以及健康教育等, 经过个性化治疗和护理干预, 确保患者成功脱机拔管, 痊愈出院。)